Beyond Success and Failure: Explaining Community-Based Tourism Stagnation through Institutional Voids - Ahsani, Retno Dewi Pramodia; Keban, Yeremias Torontuan (Universitas Teuku Umar, 2025)
This study examines the factors that explain the stagnation of community-based tourism (CBT) in Sambeng Village, part of the Balai Ekonomi Desa (Balkondes) program in Indonesia’s Borobudur super-priority tourism destination. Adopting a qualitative single-case study design, the research draws on 22 semi-structured interviews with villagers, local elites, government officials, and external stakeholders, complemented by field observations and document analysis. Findings indicate that stagnation is not the result of a single determinant but rather an interplay of interrelated conditions. Four key factors emerged: tokenistic participation that reduced villagers to symbolic roles, the absence of empowerment across economic, psychological, social, and political dimensions, institutional voids that left the Balkondes without governance anchors, and incompatibility between tourism initiatives and agrarian livelihoods. Elite competition further generated institutional inertia, leading to what this study conceptualizes as “elite paralysis,” a condition preventing both capture and mobilization. The research contributes to CBT scholarship by expanding the typology of outcomes beyond success and failure to include non-emergence under institutional voids. Empirically, it offers new insights from a neglected case in a flagship national program. Practically, it highlights the risks of infrastructure-first approaches and underscores the need for institution-building, leadership development, and trust formation to foster sustainable CBT.